Anti-Inflation Policy Benefits the Poor: Evidence from Subjective Well-Being Data - Heinz Welsch; Jan Kühling (University of Oldenburg, Department of Economics, 2011)
Using subjective well-being data for more than 91,000 individuals in 30 OECD countries, 1990-2008, we study how people's implicit aversion towards inflation varies with income and other socio-economic characteristics. While inflation aversion decreases with income, it increases with the education level. Contrary to previous findings using statedpreferencemethods, these relationships apply not only to absolute inflation aversion, but also to the aversion towards inflation relative to unemployment. These results survive several robustness checks. The differing results concerning the roles of income and education suggest that different dimensions of being disadvantaged influence the well-being effects of inflation in different ways.
Keywords: E31; E24; I31; I32; 330; inflation; unemployment; poverty; social incidence; subjective well-being